Effect of Ultrasound on the Extraction of Gallic Acid from Labisia Pumila (Kacip Fatimah) - Noor Adilah, Md Salehan; Ahmad Ziad, Sulaiman (2015)
Labisia pumila, is a genus of small woody and leafy plants belonging to the Myrsinaceae family that can widely found in the tropical forest of South East Asian countries (Lee Suan Chua et al., 2012). It has a creeping stems and is mainly found in the lowland and hill forests in Southeast Asia, particularly Malaysia, Indonesia, Thailand, Laos, Cambodia, and Vietnam (Farouk et. al., 2008) and mostly obtained from the natural tropical forest (Md Ariff et. al., 2013). Labisia pumila be recognized as a small herbaceous under a shrub that roots from the stem with a few leaves pointing upwards with the spike like panicle of small clusters of white or pink flower (Pattiram, P. D et al 2011). Labisia pumila contains a phenolic compounds (Siti Nadiah Mohd Abdah,2013) and it has been proven to have multiple biological effects, such as high antioxidant properties (Lee Suan Chua et al., 2012) and anti inflammatory activity (R.Vijayalakshmi and R.Ravindhran, 2012). The main functions of antioxidants function is to delay the oxidation processes of other molecules by inhibiting the initiation or propagation of oxidizing chain reactions by free radicals. The important phenolic compounds that helps for the process is known as Gallic acid(3,4,5-Trihydroxybenzoic acid). The antioxidant activity of benzoic acids have been reported higher than vitamin C and E agaist reactive oxygen species(Lee Suan Chua et al., 2012).The chemical formula of gallic acid is C7H6O5 with an exact molecular mass of 170.12 g/mol. Their chemical structures are shown in Figure 1.The increasing demand of herbal based product has created great opportunities for global marketing. Therefore, it is vital to identify a best extraction technique to maximize the performance of the process.